Short-term and long-term outcome of manipulation under anesthesia in primary frozen shoulder - Mandal, Malay Kumar; Sen, Abhijit; Paul, Anirban; Jash, Swagatam (Asian Journal of Medical Sciences, 2021)
Background: Painful restriction of active and passive shoulder range of motion which cannot be attributed to any internal shoulder pathology is termed as primary frozen shoulder. It has three stages – freezing stage, frozen stage, and thawing stage. Nonsteroidal anti-inflammatory drugs, physiotherapy, intra-articular corticosteroid injection, hydrodilatation, arthroscopic capsular release, and manipulation under anesthesia (MUA) are different modalities of treatment. Aims and Objectives: The main objective of our study was to assess the short-term and long-term outcome of MUA in frozen shoulder once it did not respond to 3 months course of physiotherapy. Materials and Methods: Fifty patients of primary frozen shoulder fulfilling inclusion criteria were manipulated under general anesthesia, and intra-articular Depo-Medrol and bupivacaine were administered. Functional status of the shoulder was assessed using the adjusted Constant-Murley (CM) score preoperatively and in subsequent follow-ups. Results: There was a significant improvement of mean adjusted CM score in short- and long-term follow-ups compared to pre-manipulation value. A significant negative correlation was found between the age of the patient and the final outcome. Conclusion: MUA is an effective modality of treatment in primary frozen shoulder with good short- and long-term outcomes.